The Corporate Spread Curve and Industrial Production in the United States - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2002)
The term structure of domestic investment grade bond spreads - or corporate spread curve - contains useful information to predict future changes in industrial production, beyond the information already contained in interest rates, commercial paper-treasury bill spreads, and lagged values of industrial production. In fact, the corporate spread curve can explain the cumulative growth rate of industrial production over 3- to 48-month horizons, and the marginal growth rate over 6- to 18-month horizons. Unlike other financial variables, the corporate spread curve has been a stable predictor of real activity for the last fifteen years.